Population structure, gene flow, and sex‐biased dispersal in the reticulated flatwoods salamander (Ambystoma bishopi): Implications for translocations. (27th August 2021) - Williams, Steven T.; Elbers, Jean P.; Taylor, Sabrina S.
Abstract: Understanding patterns of gene flow and population structure is vital for managing threatened and endangered species. The reticulated flatwoods salamander ( Ambystoma bishopi ) is an endangered species with a fragmented range; therefore, assessing connectivity and genetic population structure can inform future conservation. Samples collected from breeding sites ( n  = 5) were used to calculate structure and gene flow using three marker types: single nucleotide polymorphisms isolated from potential immune genes (SNPs), nuclear data from the major histocompatibility complex (MHC), and the mitochondrial control region. At a broad geographical scale, nuclear data (SNP and MHC) supported gene flow and little structure ( F ST  = 0.00–0.09) while mitochondrial structure was high (ΦST  = 0.15–0.36) and gene flow was low. Mitochondrial markers also exhibited isolation by distance (IBD) between sites ( p  = 0.01) and within one site ( p  = 0.04) while nuclear markers did not show IBD between or within sites ( p  = 0.17 and p  = 0.66). Due to the discordant results between nuclear and mitochondrial markers, our results suggest male‐biased dispersal. Overall, salamander populations showed little genetic differentiation and structure with some gene flow, at least historically, among sampling sites. Given historic gene flow and a lack of population structure, carefully considered reintroductions could begin to expand the limited range of this salamander to ensure its long‐term resilience.